KARAKTERISTIK DEMOGRAFI, SOSIAL, DAN EKONOMI KELUARGA PENERIMA PROGRAM KELUARGA HARAPAN (PKH) - Simanjuntak, Megawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2010)
Cash Conditional Transfer (PKH) is one of government's efforts to reduce poverty and improve the quality of human resources in poor communities through the provision of conditional subsidies. The purpose of this study were to identify characteristics of demographic, social, and economic of PKH families recipients and to analyze the differences of economic characteristics between pre and during families get PKH funds. This study applied a combination of cross-sectional and retrospective designs. Data collection located in eight villages in Dramaga District, Bogor Regency from March to December 2009. The sample was the wife from the families who received PKH as many as 150 people determined randomly by systematic methods. Statistical analyses were descriptive and paired t-test. Characteristics of demographic, social and economics of samples concluded from this study were the largest percentage of families ranged from five to six family member from nuclear families, as well as head of family and wife age ranged from 30 to 49 years. Their education levels were only up to primary school with head of family worked as laborers, while most wives did not work. Most family heads and wives both literacy in reading and writing Latin alphabet. Family total revenue increased significantly 1.3 fold during received PKH fund. Categories poverty did not change for the families who received PKH, but the ownership of electronic devices increased. Head of family has the largest and significant contribution to the total revenue of the family. The average expenditure per month for food and non-food respectively 70,1% and 29,9%. Significant increase for debt nearly twice as families received PKH fund. Ability to pay debt with assets owned, increased by obtaining PKH fund.